Program Mentoring Dalam Kasus Penempatan Tenaga Kerja Bermasalah Di Perpustakaan - Sujoko, Sujoko (Pustakaloka, 2015)
Mentoring program for misplacing workers at libraries dealts with the programs to to organize people in order to they can adjust of work  rhythm  in  the  library. This  study  is a part of human  resources management, making mentee (member of programs) to be independent, not dependent, and can contribute to the library. This program can be applied for same cases in the future.